(untitled) (Third Sector Social Economic Review, 2025)
The purpose of this study is to examine the articles and theses in the literature on altruistic leadership. In this context, a search was conducted on the Web of Science, PubMed, Scopus, ScienceDirect, EBSCOhost, TR Index, Google Scholar and National Thesis Center databases between 03.07.2024 and 14.08.2024 using the keywords “altruistic leadership”, “altruistic leader”, “altruistic leadership”, “altruistic leader”, “altruistic leadership” and “altruistic leader”. As a result of the analysis, 40 studies on altruistic leadership were reached, and a total of 35 studies were included in the study when the elimination was made according to the inclusion criteria. The studies obtained are qualitative research with descriptive purposes based on document analysis and systematic compilation (using descriptive content analysis) based on the criteria of publication year, type of study, publication language, variables associated with altruistic leadership and the number of variables, research methods, data collection tools, fields where the studies were conducted, samples and sample sizes, place of study, sector where it was conducted and number of references. The findings obtained from the study were interpreted and presented with tables. It is thought that the findings obtained as a result of the study will contribute to the relevant literature in terms of comprehensively evaluating the research conducted on leadership various fields and it is also aimed to fill the gap in this direction.